2022
DOI: 10.1088/1741-2552/ac6a12
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and simulation studies of localization and decoding of single and double dipoles

Abstract: Electroencephalography (EEG) is a technique for measuring normal or abnormal neuronal activity in the human brain, but its low spatial resolution makes it difficult to locate the precise locations of neurons due to the volume conduction effect of brain tissue. The acoustoelectric (AE) effect has the advantage of detecting electrical signals with high temporal resolution and focused ultrasound with high spatial resolution. In this paper, we use dipoles to simulate real single and double neurons, and further inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…In 2021, Song et al conducted a steadystate visual evoked potentials (SSVEPs) experiment in living rats based on ABI, and the experimental results showed that the decoded AE signal had high amplitude responses at both fundamental and harmonic of the visual stimulus frequency, and this experimental study realized the first millimeter spatial resolution SSVEP measurement in living rats [9]. In 2022 Zhang et al used FUS irradiation to simulate the dipole of neuronal discharge, and the simulation and experimental results showed that the localization and decoding results were highly consistent with the preset parameters, and the dipole localization error was less than 0.3 mm [10].…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…In 2021, Song et al conducted a steadystate visual evoked potentials (SSVEPs) experiment in living rats based on ABI, and the experimental results showed that the decoded AE signal had high amplitude responses at both fundamental and harmonic of the visual stimulus frequency, and this experimental study realized the first millimeter spatial resolution SSVEP measurement in living rats [9]. In 2022 Zhang et al used FUS irradiation to simulate the dipole of neuronal discharge, and the simulation and experimental results showed that the localization and decoding results were highly consistent with the preset parameters, and the dipole localization error was less than 0.3 mm [10].…”
Section: Introductionmentioning
confidence: 52%
“…Each electrode was inserted into the y = 0 section in the phantom along the y-axis direction according to the set position, where the phantom is composed of acrylamide (AM), ammonium persulfate (APS), N, N ′ -methylenebisacrylamide (MBA), and N, N, N ′ , N ′ -tetramethylethylenediamine (TEMED), egg white solution, and physiological saline [10,28]. For the single-source experiments in Dipole1+, the transducer was modulated to perform a 2 mm × 2 mm raster scan of the y = 0 cross-section in 0.2 mm steps using the array modulation method in 2.1.2 at an initial excitation voltage of 5 V for each array (purple area in figure 3(e)).…”
Section: Abi Experimental Methodsmentioning
confidence: 99%
“…Barragan used a head phantom with a real human skull to demonstrate 4D ABI for mapping time-varying monopoles and dipoles at depths >60 mm with detection thresholds <0.5 mA ( Figure 4 ) (Barragan et al, 2020 ). In 2022, Zhang used FUS irradiation to simulate the dipole of neuronal firing, and the simulation and experimental results showed that the localization and decoding results were highly consistent with the predicted situation (Zhang et al, 2022 )).…”
Section: Research Progressmentioning
confidence: 70%
“…It has been demonstrated that AEBI can map DBS currents inside human skulls submerged in 0.9% NaCl solution [24][25]. Besides, we have demonstrated that the pulse repetition frequency (PRF) of FUS is capable of encoding electroencephalography (EEG) signal and decoding AE signal and proved its feasibility through in vivo rat brain AEBI experiments [26][27][28][29][30][31]. Furtherly, based on PRF, living rat steady-state visual evoked potentials activation was mapped and the AE signal processing network of the rat brain was revealed [32][33][34][35].…”
Section: Introductionmentioning
confidence: 80%
“…In this study, PRF was used to extract AE signal from raw signal which was validated in previous work [26][27][28][29][30][31]. The voltage signals acquired at each focal spot initially were used as the raw data and was first down sampled at 5000 Hz.…”
Section: Image Protocolmentioning
confidence: 99%